The soundscape of Orthodox Christian worship: Reflections on methodology and research ethics - Lukkala, Tuuli (Journal of the International Society for Orthodox Music, 2020)
The study of Orthodox Christian worship and church music has traditionally focused on historical research, but interest in the present day and the use of ethnomusicological methods is gaining ground among scholars around the world. In Finland, only sporadic observations of church music repertoire and liturgical practices have been published so far. Worship is a multisensory experience in Orthodox Christianity, but there is a strong emphasis on sounds and the sense of hearing. Sounding prayers and hymns aloud enables some of the main purposes of worship: common prayer and the sanctification of time, which is related to the ephemerality of sounds. From a cultural stance, the short-lived sounds are signs of activity and interaction. The aim of my research is to study different aspects of the varying soundscapes of Orthodox worship: what they consist of, how participants experience them, and in what kind of contexts the soundscapes are produced and experienced. I have conducted ethnographic fieldwork in the parishes of the Orthodox Church of Finland since October 2018, participating in divine services, making audio recordings of them, and interviewing their participants. I aim to visit all 21 parishes to gain overall knowledge of the soundscapes of worship in Finland and to discover possible local variation within the church. Ethnography as a methodology lends itself well to a study in the crossroads of church music, liturgics, soundscape studies, and ethnomusicology with a secondary, archival goal of documenting cultural practices. In this paper I discuss methodological and ethical questions arising from crafting an applied research design for the study, doing insider ethnography, and participatory observation among a great number of people, and in worship, a semi-public space.